(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
The Editorial Board is delighted to announce that Yesterday&Today has made more great strides in increasing the visibility, accessibility, impact and distribution of the journal nationally and internationally. An application was submitted during March of this year and in October it was accepted into the Directory of Open Access Journals (DOAJ). The DOAJ is an online directory that indexes and provides access to quality open-access, peer-reviewed journals. The statistics show that per month more than 300 000 people from all over the world visit the DOAJ.